Oligomycins A and C, major secondary metabolites isolated from the newly isolated strain Streptomyces diastaticus - Yang, P. W; Li, M. G; Zhao, J. Y; Zhu, M. Z; Shang, H; Li, J. R; Cui, X. L; Huang, R; Wen, M. L (Folia microbiologica, 2010)
During the screening program for fungicides, one actinomycete strain ECO 00047 was isolated with the potential activity against fungus. According to the morphology and analysis of the nucleotide sequence of the 16S rRNA gene (1500 bp) this isolate was identified as Streptomyces diastaticus. The active compounds were separated by silica gel column chromatography, Sephadex LH-20 gel filtration and then purified by flash chromatography on C18 (20-45 microm). The chemical structure of the bioactive compounds I and II were elucidated, based on the spectroscopic data of MS, IR, UV, 1H-NMR, 13C-NMR and X-ray single crystal diffraction analysis. Compounds I and II were identical with oligomycins A and C, the macrolide antibiotics which have been known to be produced by Streptomyces diastatochromogenes, S. libani and S. avermitilis. The two compounds exhibited a strong activity against Aspergillus niger, Alternaria alternata, Botrytis cinerea and Phytophthora capsici but no activity toward bacteria. Although the two above antibiotics were known, their isolation has so far not been reported from S. diastaticus.
Keywords: oligomyciny; Chromatography, Liquid; DNA bakterií; DNA, Ribosomal; Phylogeny; antifungální látky; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; financování organizované; RNA ribozomální 16S; Cluster Analysis; Financing, Organized; RNA, Ribosomal, 16S; Aspergillus niger; spektrální analýza; Alternaria; Botrytis; sekvenční analýza DNA; DNA, Bacterial; chromatografie kapalinová; Antifungal Agents; fylogeneze; shluková analýza; ribozomální DNA; Spectrum Analysis; Oligomycins; Phytophthora; Streptomyces